ChemInform Abstract: Facile Synthesis of Co2P via the Reduction of Phosphate with KBH4 for Nickel‐Based Rechargeable Batteries. Issue 6 (23rd January 2015) - Wang, Yaping; Wang, Yijing; Li, Huanhuan; Liu, Zongtao; Zhang, Lili; Jiang, Haobin; Zhou, Ming; Li, Baojia; Ren, Naifei
Abstract Nanocrystalline Co2P metalloid is prepared as anode material for Ni/Co secondary batteries by reduction of a Co‐based phosphate with KBH4 (600 °C, 0.5 h).